Aristotle and Tarski - Jan Woleński (Peitho, 2017)
Alfred Tarski frequently declared that his semantic definition of truth was inspired by Aristotle’s views. The present paper discusses this issue in the context of Marian Wesoły’s criticism of the thesis that there is an affinity between Tarski’s views and those of Aristotle. The article concludes with an inquiry into whether Aristotle’s definition of truthfulness can be identified with the correspondence theory of truth.